The Anti-Vaccination Movement: A Serious Threat to Public Health - Spiliotopoulos, Nikolaos; Spiliotopoulou, Marina (HAPSc Policy Briefs Series, 2021)
The accomplishment of the ‘’herd immunity’’ is the most important challenge in the Early Post Covid World. However, the challenge becomes even more complicated when a large amount of the general population refuses to get vaccinated because of various fears and concerns. Although the digital age has numerous benefits, social media platforms can create a gap between pro-vaccination supporters and anti-vaccination supporters. The strong presence of the latter on social media can be worryingly harmful for each country’s vaccination procedure. Despite the indisputable efforts of every country to limit the spread of the vaccine hesitancy, we observe that the number of the anti-vaccination supporters has increased. As a result, this urgent and dangerous situation demands decisive actions, in order to secure public health. It is true that a lot of countries are making efforts to encourage vaccination and to combat anti-vaccination campaigns. Information about the risks and benefits, research for new vaccines, improvement of vaccine supplies are some of the strategies that the states are practicing. But are they enough? The strategies for the resolution of the problem should be more specific and more focused on the real problem. In this policy brief we suggest a number of measures that would be able to contribute to a stronger Immunization System. Some of the recommendations are the association between the WHO and vaccine manufacturers, the collaboration between public and private field, organized campaigns for vaccination, powerful online pro-vaccination campaigns, the contribution of certain specialists, the possibility to get vaccinated by other channels, simpler supply and transporting, penalties to health personnel who refuse to get vaccinated, stricter laws for ‘’herd immunity’’, assessment reports by the WHO in case of insufficient supplies.